Examination of the Effect of Memorable Travel Experiences on the Memorability of Trips and Intentions to Revisit a Destination - Tukamushaba, Eddy K. (International Journal of Technology and Management, 2022)
In this paper a model examining the effect of memorable travel experiences on the memorability and tourists’ intentions to revisit a destination is developed and tested. A sample of 500 international tourists entering Uganda through Entebbe international airport is used. A two-step approach of structural equation modeling is applied. The results obtained indicate that hedonism, novelty, refreshment, and local culture were key determinants of memorable experiences within the sample of the international tourists. The factors of involvement, meaningfulness and knowledge were not significant determinants of memorable travel experience. Secondly, memorable travel experience had a direct and positive significant effect on memorability and intention to revisit a destination. However, the relationship between memorable travel experiences and intention to revisit a destination was negative and non-significant when memorability of tourism experiences was introduced as mediator indicating incomplete mediation. Based on the results, it is suggested that destination managers should strive to develop new products that are unique within a destination in order to elicit memorable experiences. Incorporating activities that facilitate social interaction between tourists and local community within the different tourism attraction areas would be critical in enhancing memorable travel experience and therefore improving the odds of intention to revisit a destination.
Keywords: Memorable travel experiences; memorability; revisit intentions